Flexible high-density microelectrode arrays for closed-loop brain–machine interfaces: a review - Liu, Xiang; Gong, Yan; Jiang, Zebin; Stevens, Trevor; Li, Wen (Frontiers in Neuroscience, 2024)
Flexible high-density microelectrode arrays (HDMEAs) are emerging as a key component in closedloop brain-machine interfaces (BMIs), providing high-resolution functionality for recording, stimulation, or both. The flexibility of these arrays provides advantages over rigid ones, such as reduced mismatch between interface and tissue, resilience to micromotion, and sustained long-term performance. This review summarizes the recent developments and applications of flexible HDMEAs in closed-loop BMI systems. It delves into the various challenges encountered in the development of ideal flexible HDMEAs for closed-loop BMI systems and highlights the latest methodologies and breakthroughs to address these challenges. These insights could be instrumental in guiding the creation of future generations of flexible HDMEAs, specifically tailored for use in closed-loop BMIs. The review thoroughly explores both the current state and prospects of these advanced arrays, emphasizing their potential in enhancing BMI technology.